Sobre um dizer na arte: história, sentido e função no trabalho artístico - Gladston da Costa Almeida (2011)
From an uneasiness brought by the analysis of texts dealing with art and publications and interviews with artists writings, it is proposed an investigation into the role that they assume a context of art like this, it becomes significantly noticeable the relevance of the discourse takes over in the artistic practices. With the trigger language philosophy of Wittgenstein and the theoretical work of Joseph Kosuth, the objective of this work revolves around the possibility of performing a text that addresses immediate issues to the field of art making use of a language that does not shirk the condition to be built on a specific grammar regarded as the discursive universe of art. Propositions on the history of art, philosophical hermeneutics, philosophy of language and theory of art, it creates a speculative universe that is based first discuss the nature of grammar then specifies the art and even his manner of use, a context in which practices are varied and multiple objects of investigation. Concepts of the nature of art and proposing face the foundation of research unfolds the way of a speech he intends to refute the significance of the art operations, any sentence meaning unclear. And parallel to this definition it is proposed that the discursive practice in the art to carry out sentences based on the actual field of art its logical nature.